Traitement Des Investissements Étrangers Dans Les Législations Nationales: Regard Croisé Sur Les Incitatifs Du Code Burundais Des Investissements De 2008 - Nzohabonayo, Anaclet (European Scientific Journal, ESJ, 2018)
This reflection assesses the incentives of the Burundian code of investments of 2008 as for their extent and effectiveness. It shows that the 2008 Burundi Investment Code has created a favorable business climate. It provides for very generous tax and customs incentives that can influence foreign investors in the choice of destination for their investments. However, these incentives have been constantly nibbled following the entry into force of the budget laws of 2016 and 2017 and even a straddle of the general tax code of 2013. From the analysis, it appears that these incentives have lost their substance and that the 2008 code and the Free Zone Act of 2001 have become lapsed instruments that display incentives that have been flawed to the point that some have even been removed. Given the fact that there is a gap between the planned and the actual incentives, there is a need to compile these incentives to identify those that have become archaic and to redefine them to make a new one. The ultimate outcome of this work would be the revision of the investment code of 2008. It is in this respect that the Burundian legislator could reinforce predictability and transparency and keep in the logic of increasing the flow of foreign investments that can generate new sources of financing for development.